Respuesta :

here are the exponential rules:

[tex](ab)^c=(a^c)(b^c)[/tex]

[tex]\frac{1}{a^b}=a^{-b}[/tex]

[tex](a^b)^c=a^{bc}[/tex]

[tex](a^b)(a^c)=a^{b+c}[/tex]

if [tex]a^b=c^b[/tex] and b=b, then a=c


a.

she made a mistake in the 1st step because she used a positive exponent instead of a negative one for a fraction

in mathspeak: 1/16=1/(2^4)=2^-4, not 2^4



b.

[tex]2^{2x-3}=(\frac{1}{16})^{3x+9}[/tex]

[tex]2^{2x-3}=(\frac{1}{2^4})^{3x+9}[/tex]

[tex]2^{2x-3}=(2^{-4})^{3x+9}[/tex]

[tex]2^{2x-3}=2^{-4(3x+9)}[/tex]

[tex]2^{2x-3}=2^{-12x-36}[/tex]

[tex]2x-3=-12x-36[/tex]

[tex]-3=-14x-36[/tex]

[tex]33=-14x[/tex]

[tex]x=\frac{-33}{14}[/tex]

Ver imagen apologiabiology
DeanR

Leah made a mistake in the first step, writing [tex] \frac 1 {16} [/tex] as [tex]2^4[/tex] when it's really [tex]2^{-4}[/tex].

[tex] 2^{2x-3} = (2^{-4})^{3x + 9} = 2^{-12x - 36}[/tex]

[tex]2x - 3 = -12x - 36[/tex]

[tex]14x =-33[/tex]

[tex]x = -\dfrac{33}{14}[/tex]

Check:

2x-3 = -33/7 - 21/7 = -54/7

-4(3x+9) = -4(-99/14 + 126/14) = -4(27/14) = -54/7 check

Answer: x=-33/14